The recognition of a "judgment of paternity" in a case of cross-border surrogacy under German Law – commentary to BGH, 10 december 2014, az. Xii zb 463/13 - Gössl, Susanne Lilian (CUADERNOS DE DERECHO TRANSNACIONAL, 2015)
The article comments on a recent decision of the BGH (German Supreme Court) regarding the recognition of a “judgment of paternity” which was obtained by a German couple in California after concluding an agreement with a surrogate mother in California. The German law is strictly opposed to any form of surrogacy; therefore earlier courts had usually denied recognition in similar cases for ordre public reasons. In this decision the BGH decided on the matter for the first time. Contrary to the lower instance courts she recognized the “judgment” after a careful weightening of all rights and policies involved. He came to the conclusion that the preponderant interests of the child outweighed all interest opposing a denial of recognition. The article describes the legal background of surrogacy and cross-border parenthood law. Afterwards, it explains the decision and which controversial issues the BGH decided. Finally it gives an outlook on those questions the BGH did not decide and how she probably will decide if she keeps her line of argument. Key Words: surrogacy, German private international law of parentage, recognition of foreign judgments under German law. Zusammenfassung: Dieser Artikel kommentiert die Entscheidung des BGH zur Anerkennung eines “judgment of paternity”, welches ein kalifornisches Gericht zugunsten eines deutschen Pärchens ausgesprochen hatte. Diese hatten vorher eine Leihmutterschaftsvereinbarung in Kalifornien nach kalifornischem Recht abgeschlossen. Das deutsche Recht lehnt alle Formen der Leihmutterschaft ab. Die unterinstanzlichen Gerichte versagten daher regelmäßig eine Anerkennung als ordre public-widrig. Der BGH entschied das erste Mal über die Frage. Er nahm eine Abwägung aller in Frage stehenden Rechte und Interessen vor und sprach sich – im Gegensatz zu den meisten unterinstanzlichen Gerichten – für eine Anerkennung aus. Ausschlaggegebend waren die Interessen des Kindes, die alle übrigen Interessen und Rechte überwogen. Der Beitrag gibt einen Überblick über die deutsche Rechtslage, erläutert dann die Entscheidung und gibt anschließend einen Ausblick bezogen auf die Fragen, welche der BGH offen ließ. Stichwörter: Leihmutterschaft, deutsches Abstammungskollisionsrecht, Anerkennung ausländischer Entscheidungen im deutschen Recht